The Legal Organization of Juvenile Court- The Problem of Conflict with Constitutional Standards and General Procedural Rules A study for Reaching Integration - Ramadhan, Hivee Hassan (Journal of Legal and Political Studies, 2025)
This research focuses on Iraq’s juvenile legal framework, specifically the Juvenile Court’s structure and its jurisdiction. Because of to its age-specific mandate, this court differs from ordinary courts, this causes conflicts with the Iraqi Constitution of the year 2005 and procedural rules, creating legal obstacles. The study analyzes constitutional and legal issues of Article 54 of the Juvenile Welfare Law and suggests reforms to ensure compliance. Keywords: Juvenile court, court committee, jurisdiction, constitution, legal principles.
Keywords: Juvenile court; court committee; jurisdiction; constitution; legal principles